Role of foreign aid for poverty alleviation - Hossain, A S M Sohrab (KDI School, 2011)
Development economics could not able to give any direct answer about the impact of foreign aid on poverty alleviation specifically. Different economists opined differently. Some argued that it has a positive impact on poverty alleviation or economic growth and some opposed that. In consideration with the alleviation of poverty of Bangladesh through foreign aid is still an unresolved issue. Bangladesh is one of the poorest countries in the world. Bangladesh has received a huge amount of foreign aid since her independence in 1971 from various country of the world for economic development. Although Bangladesh achieved some specific areas of progress but still aggregate poverty rates remain dauntingly high. Pockets of extreme poverty persist. Inequality is a rising concern. The paper examines the effectiveness of foreign aid in eradicating poverty through human poverty indicators in Bangladesh. In this paper the basic questions which will be discussed about is 'does foreign aid play any role to eradicate poverty in Bangladesh?'
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Bangladesh.